2007
DOI: 10.1182/blood-2006-05-022111
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in DNA repair genes and therapeutic outcomes of AML patients from SWOG clinical trials

Abstract: Repair of damage to DNA resulting from chemotherapy may influence drug toxicity and survival in response to treatment. We evaluated the role of polymorphisms in DNA repair genes APE1, XRCC1, ERCC1, XPD, and XRCC3 in predicting therapeutic outcomes of older adults with acute myeloid leukemia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Until recently, genetic variants involved in drug metabolism or DNA repair were considered the main possible modifiers of treatment outcome. [21][22][23] Single nucleotide polymorphisms of genes involved in hematopoietic signal-transduction were investigated less frequently. 24,25 In this study, we report an association of the JAK2 46/1 haplotype with disease characteristics and treatment out- 26,27 Retrieving haplotype information from the HapMap Project on rs12343867 and rs2230724 in a Chinese population revealed that the above polymorphisms are not in complete linkage (estimated haplotype frequencies of rs12343867/rs2230724: T/G: 57%, C/A: 23%, T/A: 18%, C/G: 2%, D': 0.892; P<0.000).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, genetic variants involved in drug metabolism or DNA repair were considered the main possible modifiers of treatment outcome. [21][22][23] Single nucleotide polymorphisms of genes involved in hematopoietic signal-transduction were investigated less frequently. 24,25 In this study, we report an association of the JAK2 46/1 haplotype with disease characteristics and treatment out- 26,27 Retrieving haplotype information from the HapMap Project on rs12343867 and rs2230724 in a Chinese population revealed that the above polymorphisms are not in complete linkage (estimated haplotype frequencies of rs12343867/rs2230724: T/G: 57%, C/A: 23%, T/A: 18%, C/G: 2%, D': 0.892; P<0.000).…”
Section: Discussionmentioning
confidence: 99%
“…El-Din et al (2010) observed that AML patients expressing XRCC1 Arg194Trp polymorphism are at high risk of developing AML; in addition, a significant risk in the development of AML was observed when XRCC1 Arg399Gln polymorphism was present. In a study of 372 patients with acute myeloid leukemia, Kuptsova et al (2007) reported no significant associations between XRCC1 polymorphisms and treatment outcomes.…”
Section: Xrcc1mentioning
confidence: 99%
“…Of course, this controversy might be explained by different patient groups involved in these studies and it could be claimed that XPD Lys751Gln is a predictor of poor response to front line chemotherapy only in patients with normal karyotype. Among other polymorphisms, XPD Asp312Asn is reported to have a positive impact on drug effectiveness (Kuptsova et al 2007) and XPC Ala499Val has been associated with decreased overall survival in AML patients with normal karyotype (Strom et al 2010). Furthermore, in a study that included 110 AML patients, patients with XPA genotype -4A>G have been shown to have a higher frequency of chemoresistant disease when compared to wild type carriers (30% vs. 6, 5 % genotype AA) (Monzo et al 2006).…”
Section: Dna Repair Deficiency Related To Hematological Malignanciesmentioning
confidence: 99%
“…Although there has been much effort on identifying DNA repair polymorphisms that could predict chemotherapy effectiveness in order to allow appropriate selection of drugs in specific patients, the existing results are of no clinical use and are sometimes contradictory. For example, polymorphism XPD Lys751Gln has been correlated with reduced risk of resistant disease (RD) due to an increased chemotherapy response rate (Kuptsova et al 2007). However, in another study, the same polymorphism has also been associated with poor response to chemotherapy and decreased survival in patients with intermediate risk AML and normal cytogenetics (Strom et al 2010).…”
Section: Dna Repair Deficiency Related To Hematological Malignanciesmentioning
confidence: 99%